2011
DOI: 10.1007/bf03256922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ipragliflozin (ASP1941), a Novel Selective Sodium-Dependent Glucose Co-Transporter 2 Inhibitor, on Urinary Glucose Excretion in Healthy Subjects

Abstract: Administration of ipragliflozin was well tolerated and resulted in a rapid, dose-dependent increase in glucosuria. Pharmacodynamic and pharmacokinetic data suggest that ipragliflozin is suitable for prolonged once-daily oral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 29 publications
5
32
0
Order By: Relevance
“…t 1/2 , CL/F, and, Vd/F were 7.6 ± 2.0 h, 0.38 ± 0.13 L/h/kg, and, 4.4 ± 2.6 L/kg, respectively, and the plasma concentration of ipragliflozin 24 h after the oral administration of ipragliflozin to rats (22.9 ± 5.2 ng/mL) was determined. These pharmacokinetic parameters in rats were relatively close to those in humans [1,4,12]. These results suggest that the assay method is valuable for evaluating the pharmacokinetics of ipragliflozin in rats.…”
Section: Pharmacokinetic Parameterssupporting
confidence: 53%
See 1 more Smart Citation
“…t 1/2 , CL/F, and, Vd/F were 7.6 ± 2.0 h, 0.38 ± 0.13 L/h/kg, and, 4.4 ± 2.6 L/kg, respectively, and the plasma concentration of ipragliflozin 24 h after the oral administration of ipragliflozin to rats (22.9 ± 5.2 ng/mL) was determined. These pharmacokinetic parameters in rats were relatively close to those in humans [1,4,12]. These results suggest that the assay method is valuable for evaluating the pharmacokinetics of ipragliflozin in rats.…”
Section: Pharmacokinetic Parameterssupporting
confidence: 53%
“…1) is a highly potent and selective sodium-dependent glucose co-transporter-2 (SGLT2) inhibitor, a novel class of hypoglycemic agents [1][2][3][4]. SGLT2 inhibitors suppress glucose re-absorption in the proximal tubules of the kidney and promote the urinary excretion of glucose; therefore, SGLT2 inhibitors may reduce blood glucose levels and body weight [1][2][3][4]. Tahara et al previously reported that ipragliflozin improved diabetes/obesity-associated metabolic abnormalities in type 2 diabetic mice, which suggests that ipragliflozin may be valuable in the treatment of type 2 diabetes with metabolic syndrome [5].…”
Section: Introductionmentioning
confidence: 99%
“…The SGLT2 EC 50 SAR was similar to that of analogs of 17; however, the SGLT1 selectivities, which ranged from 100 to 500, were somewhat reduced suggesting that the constraints imposed by the anhydro pyranose structure did not impact SGLT2 affinity but enhanced SGLT1 affinity with the result being diminished SGLT1 selectivity. The Egret/Chengdu group, having been encouraged by the activity of 6-3, also synthesized 6-4 to better assess the potential of this series.…”
Section: Sglt2 Inhibitors In Developmentmentioning
confidence: 69%
“…64 Likewise the SAR for thiazoles as a surrogate central ring was not encouraging. 64 C2 50 was also 1-2 nM, as reference compounds, the Pfizer group systematically evaluated the impact on SGLT2 affinity following changes in substitution for each of the five pyranosyl carbons of glucose. 65 The results summarized in Table 3.4 revealed that modifications of C5 produced relatively minor reductions in SGLT2 affinity.…”
Section: Replacement Of the Central Aryl Ringmentioning
confidence: 99%
See 1 more Smart Citation